L'invention rhétorique dans la Rhetorique françoise faicte particulierement pour le roy Henri III de Germain Forget - Nassichuk, John (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2008)
This article examines the place given to the part of rhetoric known as "invention" in the Rhetorique françoise faicte particulierement pour le roy Henry III, a treatise which has been attributed to the jurist Germain Forget. First, this study underlines the relative importance, in Forget's treatise, of this category which traditionally occupies the first place in the ordered disposition of ancient rhetorical treatises. In comparison, reference is made to two other contemporary treatises. Then, second, the analysis shows that the author favours a general idea of invention setting it apart from the technical considerations pertaining to specific theories of "causes". Finally, the third part of the study proposes the hypothesis that this general idea of invention, inspired by Quintilian, bears the stamp of contemporary Humanism, in particular that of the adherents, in the tradition of Erasmus and Politian, to the theory commonly known as "innutrition". At a time when the last of the Valois kings ardently wished to become a father, even commanding that public prayers be recited to this effect, the theory of rhetorical invention rests, perhaps appropriately, on humanist ideas concerning pedagogy.